Hak Pekerja Atas BPJS Ketenagakerjaan Berdasarkan Undang-Undang Nomor 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Imani Septianingsih; H. Zaeni Asyhadie; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2023)
This research aims to understand the essential considerations for adding a pension security program with legal consequences for employers who do not include workers in the pension security program based on Law Number 24 of 2011. This study uses a normative research method using a statutory, conceptual, and case approach. The results are that the addition of a pension security program to Law Number 24 of 2011 is a representation of the international convention , the mandate of Article 28 letter h paragraph (3) of the 1945 Constitution, Articles 22 and 25 of the Universal Declaration of Human Rights. As for the legal consequences are criminal penalties and administrative sanctions.Keywords: Employee Rights, Pension Guarantee, Legal Consequences.